2022
DOI: 10.1177/11786361221106111
|View full text |Cite
|
Sign up to set email alerts
|

An Eight Year Clinico-Microbiological Retrospective Study on Brain Abscesses in India

Abstract: Background: Intracranial abscesses have been a diagnostic and therapeutic challenge since time immemorial for both the microbiologists and the neurosurgeons. There is paucity of detailed studies documenting the infecting organism causing brain abscesses in South India. Aims: The study aimed at identifying and assessing the prevalence of aerobic, anaerobic bacteria and fungi associated with brain abscesses at a tertiary care hospital in South India. Methods and Material: Eight years data was collected from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In a study conducted on the pediatric population in 2021 by Kanu et al, the most prevalent symptoms noted were headache (80%), fever (78%), and hemiparesis (78%). 11 Our study showed a similar trend of common presentation with headache (90.6% vs 93.3% at first presentation and 2 nd presentation for reaspiration respectively) being the most common symptom followed by fever (81.2% aspiration vs 53.3% re-aspiration), vomiting (51.5% aspiration vs 33.3% re-aspiration), seizures (32.8% aspiration vs 26.6% re-aspiration), ALOC (23.4% aspiration vs 20% re-aspiration) and focal neurological deficit (18.7% aspiration vs 0% re-aspiration). The clinical presentation of these abscesses is dependent on the size and location of the abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on the pediatric population in 2021 by Kanu et al, the most prevalent symptoms noted were headache (80%), fever (78%), and hemiparesis (78%). 11 Our study showed a similar trend of common presentation with headache (90.6% vs 93.3% at first presentation and 2 nd presentation for reaspiration respectively) being the most common symptom followed by fever (81.2% aspiration vs 53.3% re-aspiration), vomiting (51.5% aspiration vs 33.3% re-aspiration), seizures (32.8% aspiration vs 26.6% re-aspiration), ALOC (23.4% aspiration vs 20% re-aspiration) and focal neurological deficit (18.7% aspiration vs 0% re-aspiration). The clinical presentation of these abscesses is dependent on the size and location of the abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…11 Otogenic infections are among the highest risk factors for brain abscess, according to Chetty et al, and chronic suppurative otitis media (CSOM) is one of the conditions that can lead to cerebellar brain abscesses. 12 According to the examination, the patient's otorrhea from the ear was never addressed. Otorrhea intermittently appears, is thick, yellow-green in color, and stinks.…”
Section: Discussionmentioning
confidence: 99%
“…Even radiological characteristics can occasionally be mistaken for brain tumors. 12,16 Pus builds up in the cerebrum or cerebellum and is known as an intracranial abscess. A pyogenic bacterium that develops as a result of an inflammatory process in the middle ear cavity is the cause.…”
Section: Discussionmentioning
confidence: 99%